2014
DOI: 10.5137/1019-5149.jtn.9752-13.1
|View full text |Cite
|
Sign up to set email alerts
|

Additional value of fdg-pet in epilepsy surgery: consistency and postoperative results compared with MRI and eeg

Abstract: AIm: Surgery is a treatment option for medically intractable epilepsy patients. Abnormalities in regional cerebral glucose metabolism, as identified by 18-fluorodeoxyglucose positron emission tomography (FDG-PET) have predictive prognostic value in evaluating the outcome of epilepsy surgery. This study investigated the efficacy of FDG-PET for delineation of the epileptogenic zone (EZ) by comparing its consistency with other diagnostic tools and surgical outcome. mATErIAl and mEThOds: We analyzed the results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(43 citation statements)
references
References 9 publications
2
38
2
1
Order By: Relevance
“…This corroborates previously reported observations, including: (1) FDG-PET studies which have consistently highlighted a metabolic deterioration of frontal and anterior cingulate cortices with age [9,17,18] and (2) morphometric studies where a global brain atrophy was documented with age, but with a predominance in the prefrontal cortex [19], and to a lower extent in parietal, temporal and insular grey matter areas [20][21][22]. Furthermore, the relative sparing of FDG uptake in amygdalohippocampal complexes and entorhinal cortices observed in the present study are also in accordance with the findings from previous FDG-PET studies [21,[23][24][25][26].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…This corroborates previously reported observations, including: (1) FDG-PET studies which have consistently highlighted a metabolic deterioration of frontal and anterior cingulate cortices with age [9,17,18] and (2) morphometric studies where a global brain atrophy was documented with age, but with a predominance in the prefrontal cortex [19], and to a lower extent in parietal, temporal and insular grey matter areas [20][21][22]. Furthermore, the relative sparing of FDG uptake in amygdalohippocampal complexes and entorhinal cortices observed in the present study are also in accordance with the findings from previous FDG-PET studies [21,[23][24][25][26].…”
Section: Discussionsupporting
confidence: 95%
“…Indeed, the impact of age on frontal and temporal glucose metabolism should be considered when analysing patients with possible frontal and/or temporal diseases, such as those with temporal lobe epilepsy [25], Alzheimer's disease [26], frontotemporal lobar degeneration [27] or schizophrenia [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, SISCOM data were not available for this study. In comparison, previous PET studies (conducted mainly in nonoperated adults) demonstrated 43–68% localization of the anatomic location of a structural lesion over MRI data …”
Section: Discussionmentioning
confidence: 64%
“…In comparison, previous PET studies (conducted mainly in nonoperated adults) demonstrated 43-68% localization of the anatomic location of a structural lesion over MRI data. [20][21][22] The localizing power of 3D-ESI in patients undergoing temporal resection was particularly significant. 3D-ESI in temporal lobe patients showed superior localizing power compared to PET and iSPECT.…”
Section: Discussionmentioning
confidence: 99%
“…In der klinischen Routine findet die 18 F-FDG-PET Anwendung in der interiktalen Anfallsursprungslokalisation bei fokalen Epilepsien. Der Glukosemetabolismus wird hierbei mit einer iktalen Perfusionsuntersuchung mittels 99 m Tc-ECD oder 99 m Tc-HMPAO-SPECT korreliert, um anhand der dargestellten Abweichungen zum übrigen Kortex eine genauere Eingrenzung des Anfallsursprungs vornehmen zu können [49] (siehe ▶ Abb. 4).…”
Section: Epilepsieunclassified